Is asthma in athletes a new asthma phenotype? - Sastre, B. (Journal of Allergy and Clinical Immunology, 2011)
High prevalence of asthma has been detected in athletes compared with non-athletes asthmatic subjects (NAAS). Elite athletes presented more airway hyperresponsiveness to methacholine than NAAS. However, underlying mechanisms are unknown. Our objectives were to evaluate differences in immunological and cellular mechanisms and to study functional characteristics in these patients.